Instrument development to measure the use of hologram-based learning media - Rian Vebrianto; M Yusriadi; Adisti Yuliastrin (Universitas Negeri Yogyakarta, 2023)
Hologram-based learning media is one of the alternative learning media that can be used as educational media, increasing student motivation and interest in learning and optimizing the division of work in groups. This media was developed to avoid abstract thinking, a negative impression that has been allowed to occur since they were young, which, in the end, until adulthood, the negative image is dull and makes students uninterested in things. This research was included as developmental research or RnD. Studies related to developing instruments to measure the use of hologram-based learning media as educational media in elementary schools still need to be completed.Â The research model used in this study was 4D. The data was collected with an offline questionnaire, and then it was analyzed using quantitative data analysis using the SPSS version 23 for Windows program. The results of this study have proven that: (1) The evaluation instruments construction and development for the use of hologram-based learning media for students in this study were carried out using a theoretical development model to test seven research constructs, namely (a) didactic components, (b) construction of hologram-based learning media, (c) technical hologram-based learning media, (d) ease of use, (e) efficiency of hologram-based learning media, (f) benefits, and (g) interest; (2) The results of construct validity and reliability testing show that the validity of the evaluation instrument has met the valid criteria because the value of r-count r-table (r-count 0.254); and (3) The reliability of the evaluation instrument which has been compiled and developed in this study has also met the high category as indicated by the magnitude of the Cronbach alpha reliability coefficient of 0.980. This indicates that the instrument developed meets the requirements for measuring the use of hologram-based learning media for students.